Lavender Essential Oils (LEO) as Adjunctive Therapy for Cognitive Disorders: A Study of Dopaminergic and Olfactory Pathways - Hermanto, Syalsabila Yumnaningtyas; Algristian, Hafid (Journal of Health Literacy and Qualitative Research, 2025)
Cognitive impairment is a hallmark of several psychiatric disorders, including depression and schizophrenia, and is frequently associated with disruptions in dopaminergic signaling and neuroplasticity. These cognitive deficits, affecting attention, memory, and executive functions, often persist despite pharmacological treatment. Emerging evidence suggests that non-pharmacological interventions, such as aromatherapy, may offer novel pathways to enhance cognitive function. This systematic review investigates the therapeutic potential of Lavender Essential Oil (LEO) as an adjunctive treatment, focusing on its capacity to modulate dopaminergic transmission and stimulate olfactory pathways. LEO contains bioactive compounds primarily linalool and linalyl acetate which have demonstrated neuroprotective, anti-inflammatory, and neuromodulatory effects. Through interaction with the ERK/MAPK signaling cascade and upregulation of brain-derived neurotrophic factor (BDNF), LEO enhances synaptogenesis and neuroplasticity. Additionally, olfactory stimulation by LEO promotes increased alpha and theta brainwave activity, which is associated with improved focus and memory encoding. The reviewed studies highlight both preclinical and clinical evidence supporting LEO’s role in cognitive restoration. However, while promising, further high-quality clinical trials are needed to determine standardized dosages, delivery methods, and long-term safety. Integrating LEO into multimodal cognitive therapy frameworks may present a compelling complement to conventional treatments, particularly for patients with treatment-resistant cognitive symptoms.Cognitive impairment is a hallmark of several psychiatric disorders, including depression and schizophrenia, and is frequently associated with disruptions in dopaminergic signaling and neuroplasticity. These cognitive deficits, affecting attention, memory, and executive functions, often persist despite pharmacological treatment. Emerging evidence suggests that non-pharmacological interventions, such as aromatherapy, may offer novel pathways to enhance cognitive function. This systematic review investigates the therapeutic potential of Lavender Essential Oil (LEO) as an adjunctive treatment, focusing on its capacity to modulate dopaminergic transmission and stimulate olfactory pathways. LEO contains bioactive compounds primarily linalool and linalyl acetate which have demonstrated neuroprotective, anti-inflammatory, and neuromodulatory effects. Through interaction with the ERK/MAPK signaling cascade and upregulation of brain-derived neurotrophic factor (BDNF), LEO enhances synaptogenesis and neuroplasticity. Additionally, olfactory stimulation by LEO promotes increased alpha and theta brainwave activity, which is associated with improved focus and memory encoding. The reviewed studies highlight both preclinical and clinical evidence supporting LEO’s role in cognitive restoration. However, while promising, further high-quality clinical trials are needed to determine standardized dosages, delivery methods, and long-term safety. Integrating LEO into multimodal cognitive therapy frameworks may present a compelling complement to conventional treatments, particularly for patients with treatment-resistant cognitive symptoms.